The Functions and Values of the Oral Legend 'Mbah Boyo Pati and the Catfish': A Sociological Literary Analysis - Rhesma Fahana Mahamuri; Pasiyah Tahe; Siti Haja (UIN Raden Mas Said Surakarta, Indonesia, 2025)
Oral literature in Indonesia is a form of literary expression characterized by its unique traits, functions, and values, which reflect the behaviors and cultural life of Indonesian society. One such example is the oral legend of Mbah Boyo Pati and the Catfish, found in Medang Village, Lamongan, East Java. This study examines the legend through the theoretical framework of functions and values of oral literature as proposed by William R. Bascom. A descriptive qualitative method was employed, with data presented in narrative form. The legend of Mbah Boyo Pati and the Catfish, as it circulates within the Lamongan community, serves as the primary object of analysis. Data were collected through observation, interviews, and documentation. The data analysis process included: (1) data reduction, (2) data presentation, and (3) drawing conclusions based on William R. Bascom's theory. The results indicate that the legend serves four main functions: (1) entertainment, (2) means of legitimizing social institutions and cultural practices, (3) educational means for children, and (4) enforcement and monitoring of societal norms. Furthermore, the legend conveys three core life values: (1) the value of human life as individuals, (2) the value of human life as social beings, and (3) the value of human life in relation to God Almighty. In conclusion, the study highlights the significant role and positive impact of the legend within the local community, as evidenced by the oral preservation of the story and the continued maintenance of Mbah Boyo Pati’s burial site in Medang Village, Lamongan, East Java. Sastra lisan di Indonesia merupakan salah satu bentuk kesusastraan yang memiliki karakter, fungsi, dan nilai yang didapat berdasarkan representasi perilaku kehidupan masyarakat Indonesia, salah satu sastra lisan tersebut adalah legenda “Mbah Boyo Pati dan Ikan Lele” yang ditemukan di Desa Medang, Kabupaten Lamongan, Jawa Timur. Penelitian ini dilakukan untuk legenda